Self-regulation as a context of critical thinking in cyberpolice officers - О. V. Medvedieva (Law and Safety)
The results of a study of self-regulation in the context of critical thinking in cyberpolice are presented. It is theoretically proven that self-regulation is one of the central components of critical thinking, and the interaction of these phenomena enhances the effectiveness of each of them. It is noted that the developed critical thinking and self-regulation acquire special significance in the professional activity of the police.